The Position of Justice Collaborator to Reveal Corruption in Financial Management of Regional Government - Nurma Rosyida; Kadek Deddy Permana Artha; Lintang Yudhantaka (Yuridika, 2019)
Regional autonomy that Indonesia government has implemented gives an authority to the regional government to manage their governmental affairs, including those related to their local financial management. This authority, however, is not well organized. Recently, corruption is increasingly found in local financial management, and it involves many parties within. To overcome such issue, the law enforcers may consider justice collaborator to define who the real culprit is, and thus, it needs particular criteria that refer to corruptors in the financial management of regional government. Therefore, this paper aims to analyze the key actor of corruption in the financial management of the regional government to determine justice collaborator. Using statute, conceptual, and case approaches, it finds that to determine the justice collaborator, it should identify the culprit. The criteria of corruptor in the financial management of regional government involve having a high position and dominant (influential) roles in making the crime happen, and may stop or continue the crime.